FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN IPDN KAMPUS SUMATERA BARAT - Tun Huseno (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2016)
This research was aimed to examine the effect of factors of job satisfaction onorganizational commitment of Domestic Governance Institute Employees, West SumateraCampus. Specifically, the aims of the research were (1) to find out the effect of factors ofjob satisfaction, which were the mentally challenging work, equitable rewards, supportiveworking conditions, supportive colleagues, personality-job fit on organizationalcommitment in Domestic Governance Institute Employees, West Sumatera Campus, (2) tofind out the most influential factor of job satisfaction on organizational commitment inDomestic Governance Institute Employees, West Sumatera Campus.This research was a case in Domestic Governance Institute Employees, WestSumatera Campus. The population of research was all employees of Domestic GovernanceInstitute Employee, West Sumatera Campus, their numbers were 41 employees. The sampleof the research was chosen with using the census method. Of the 41 questionnaires weredistributed to 41 respondents. The data ware collected using a validity and reliable surveyinstrument. All of the scales described below were responded to on a 5-point Likert typescale. The anchor were strongly agree (5) and strongly disagree (1). The technique ofanalysis was applied the multiple regression with the SPSS (Statistical Product and ServiceSolutions).The result of this research showed there were two the results of the research. First,the result of the research showed that the organizational commitment (Y) in DomesticGovernance Institute Employees, West Sumatera Campus was influenced in 46 % byfactors of job satisfaction which mentally challenging work (X1), equitable rewards (X2),supportive working conditions (X3), supportive colleagues (X4), and personality-job fit (X5).Whereas the remains of the organizational commitment (Y) was influenced in 54 % by theunknown and excluded factors in this model of research. Second, the result of the researchshowed organizational commitment (Y) in Domestic Governance Institute Employees, WestSumatera Campus was the most influential by the personality-job fit (X5).Keywords : mentally challenging work, equitable rewards, supportive workingconditions, supportive colleagues, personality job fit and organizationalcommitment